Government public relations strategy in the digital age: Social Media Influencer (SMI) collaboration in building community participation in Madiun Regency - Salsabila, Oka Lintang; Hastjarjo, Sri; Satyawan, Ignatius Agung (Universitas Negeri Yogyakarta, 2024)
The Madiun District Government held the Bulan Timbang Serentak as a step to identify and prevent stunting early on. There is a problem of low participation in the program so a more effective promotion strategy is needed. However, there is a problem of low participation in participating in the program so a more effective promotion strategy is needed. In this case, the public relations department of the Madiun District Government collaborated with social media influencers/SMIs to help the Bulan Timbang Serentak campaign. The purpose of this study is to describe the Madiun Regency Government's Public Relations Strategy in campaigning for Bulan Timbang Serentak with Influencers to build public participation. The method used is descriptive qualitative with a case study research type. The research data was collected by interviewing authorized officials in the Madiun District Government, namely Madiun District Government Public Relations and one of the SMI account owners with the highest engagement who collaborated in campaigning for the Bulan Timbang Serentak. To explore the strategy, the researcher used the Four Steps of Public Relations Theory (Cutlip et al., 2006). In general, the results showed that the Madiun District Government Public Relations applied the Four Steps of Public Relations in conducting its strategy.